Premilinary Studies on Phytochemical Screening of Ulam and Fruit from Malaysia - Liliwirianis N.; Nor Lailatul Wahidah Musa; Wan Zuraida Wan Mohd Zain; Jamaluddin Kassim; Syaikh Abdul Karim (E-Journal of Chemistry)
Alkaloids, saponins, steroid, terpenoid, flavonoids, phenolic distribution in 14 Malaysian favourite ulam and fruit belonging to different families were assessed and compared. The plants investigated were parkia speciosa (petai), solanum torvum (terung pipit), pithecellobium bubalinum (kerdas), moringa oleifera (kacang kelor), dryobalanops oblongifolia (keladan), cosmos caudatus (ulam raja), mentha arvensis (pudina), ocimum sp. (selasih), cymbopogon nardus (serai wangi), eugenia polyantha (serai kayu), Barringtonia scortechinii, (Putat), musa sp. (pisang), talinum paniculatum (akar som) and phyllanthus acidus (cermai). Moringa oleifera leaf and dryobalanops oblongifolia fruit were found contain positive reactions of alkaloids. All the samples studied also show high content of saponin except in bark and seed of parkia speciosa and stem of phyllanthus acidus. Meanwhile, results of the phytochemical screening on saponins, steroids, terpenoids, phenolic and flavonoids showed that cosmos caudatus, ocimum sp., mentha arvensis, barringtonia scortechinii and moringa oleifera were the active compounds present in the leaves of the plant.